Synthesis and Characterization of Hexathiosianatoiron(II) [Fe(NCS)6] 4- Complex Compound and Tetrapyridindithiosianatoiron(II) [Fe(NCS)2(Py)4] Complex Compound - Febrianti, Fitria; Sutiani, Ani; Jahro, Iis Siti; Nugraha, Asep Wahyu; Fadhila, Nabila Nur (Universitas Negeri Medan, 2024)
This research aims to synthesize and characterize the complex compounds Hexathiocyanatoiron(II) [Fe(NCS)6] 4- and Tetrapyridinedithiocyanatoiron(II) [Fe(NCS)2(Py)4]. The synthesis of these complex compounds was conducted in the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Medan State University, while magnetic susceptibility measurements were carried out using the Magnetic Susceptibility Balance (MSB) instrument in the Inorganic Chemistry Laboratory, Bandung Institute of Technology. The complex compound synthesis involved the reaction of Iron(II) sulfate heptahydrate with Potassium thiocyanate and Pyridine compound in a 1:2 and 1:2:4 molar ratio. The synthesis process was conducted through a direct reaction method in a polar solvent. The obtained results include Hexathiocyanatoiron(II) complex compound, [Fe(NCS)6] 4-, which is pale yellow crystalline with a yield of 32.76%, and Tetrapyridinedithiocyanatoiron(II) complex compound, [Fe(NCS)2(Py)4] which is dark purple crystalline with a yield of 52.62%. These compounds exhibit a melting point of 219℃. Magnetic susceptibility measurements using the MSB instrument revealed a magnetic susceptibility of 6.69 BM (paramagnetic) for the Hexathiocyanatoiron(II) complex[Fe(NCS)6] 4-, and a magnetic moment of 5.61 BM (diamagnetic) for the Tetrapyridinedithiocyanatoiron(II ) complex [Fe(NCS)2(Py)4].